1997
DOI: 10.1001/archsurg.1997.01430330104019
|View full text |Cite
|
Sign up to set email alerts
|

Ileocecal Interpositional Graft as Gastric Replacement After Total Gastrectomy and Distal Esophagectomy

Abstract: The ileocecal interpositional graft is an alternative method for replacing the distal esophagus and the stomach. A pedunculated ileocecal interpositional graft rotated 180 degrees clock-wise and placed across the hiatus between the proximal esophagus and the duodenum could act as a reservoir and protect against reflux (ileocecal valve) while preserving the duodenal passage. Two patients underwent this operation (the first patient has been observed for 12 postoperative months). We also used this technique to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…Using IIG in two patients, von Flüe [14] reported that reflux was not provoked even in the anti-Trendelenburg position. Pediatric surgeons have reported excellent results in replacing the entire esophagus with the retrosternal ileocolonic conduit.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Using IIG in two patients, von Flüe [14] reported that reflux was not provoked even in the anti-Trendelenburg position. Pediatric surgeons have reported excellent results in replacing the entire esophagus with the retrosternal ileocolonic conduit.…”
Section: Discussionmentioning
confidence: 97%
“…Hunnicutt [12] performed 4 operations on humans with minimal risks. The ileocecal segment has rarely been used with this finality, but some studies have reported good results in children [13] and in adults [14][15][16][17]. In this study we tested two interpositional pouches with reestablishment of the duodenal passage, whose advantages have been frequently described [7,20].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been used as a substitute for stomach and distal esophagus replacement[ 14, 15]. Ileocecal interposition has been demonstrated not to alter gastrointestinal transit [16].…”
Section: Discussionmentioning
confidence: 99%
“…However, in the surgical technique of Maki et al [4] alkaline esophagitis due to reflux of duodenal juice was reported because LES was removed, though the pyloric sphincter was preserved. In addition, there were cases with reflux symptoms in which the food content that flowed into the interpositioned jejunum flowed back into the esophagus, and cases in which microgastria occurred because of decreased retention due to single jejunal crus, and therefore, many cases have been reported with low QOL [1,8,[12][13][14][15][16]. The authors attempted to preserve LES in addition to the surgical technique of Maki et al [4].…”
Section: Discussionmentioning
confidence: 99%